Implanta????o de escrit??rio de projetos em institui????o de ensino superior: estudo de caso - S??, Eduardo Vimercati de (2015)
The project management area is booming and the implementation of a Project Management Office (PMO) or Project Management Office in a higher education institution (HEI) has the distinction of joining effective practices for project management to scientific knowledge and technological produced by it, contributing to the achievement of positive results for society and for institutional strengthening. This paper presents an experience lived by a higher educational institution, from which it was possible to present the implementation of project milestones of your PMO, difficulties and process facilities, as well as the specific features and functions of the project management office implemented. In addition, the discussion of the PMO characteristics in an HEI and the presentation of the use of tools capable of facilitating a PMOs deployment plan in IES, allowing its expansion to other institutions, but also discuss the most relevant issues to the literature, for example: growth of IES, project management as a tool to optimize the organization and implementation of various projects generated in institutions. Thus, this study aims to contribute to the reduction of a gap in knowledge regarding "how to deploy PMOs in HEI" which is the research question of this study. To answer this research question, applied scientific research was used with a qualitative and exploratory approach. The single case study method was applied. This scientific methodology is a type of social research empirically based, contemplated and carried out through an action that aims to solve a collective problem, in which researchers are involved in a cooperative or participatory mode (Michel, 2009). The use of single case study allowed the correlation of the theoretical framework studied with the action of the PMO implementation of IES. The research resulted in the suggestion of a project management office deployment plan in higher education institutions. And in designing "templates" from the experience of the PMOs deployment in other organizations by the HEI PMO together with studies carried through training with students and professionals from various organizations in order to draw up plans to deploy PMOs from an evaluation process such as: level of maturity, the existing PMO type and the organization structure.